Stall Evolution Mechanism of a Centrifugal Compressor with a Wide-Long Vaneless Diffuser - Zhang, Lei; Kang, Jiacheng; Lang, Jinhua; An, Guangyao; Zhang, Qian; Wang, Longyao; Wang, Qifang (Journal of thermal science, 2024)
The rotating stall mechanism is of high importance for the stability of centrifugal compressors and thermal power cycles. The majority of research concerning this topic has concentrated on the initial stall phase. However, the evolution of stall cells in wide-long diffusers has not been comprehensively studied. In this paper, the causes of rotating stall in the wide-long diffuser and the three-dimensional evolution mechanism of stall cells during the stall process were thoroughly analyzed. During the stall induction phase, an annulus vortex structure was found in the reverse-flow zone near the hub side of the diffuser outlet, which was the initial form of stall cells. The whole evolution process of stall cells was divided into three phases as the flow rate decreased. During the initial stall phase, the dynamic equilibrium was built under effects of the impeller wake and the adverse pressure gradient. As a result, the number of stall cells was kept at seven and the size of stall cells remained constant. During the transition phase, the flow in the diffuser became unstable. Stall cells extended to the impeller outlet, and the effect of the wake flow was strengthened significantly. Stall cells started integrating and separating regularly. As a result, the number and propagation speed of stall cells varied periodically at a constant mass flow rate. During the deep stall phase, the size of stall cells remained unchanged, and the number of stall cells kept at one. This study has important practical guidance and engineering value for the high-efficiency design and safe operation of centrifugal compressors.